2020
DOI: 10.1016/j.heliyon.2020.e05783
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational, electronic, spectroscopic properties, and NBO analysis of p-xylene, 3,6-difluoro-p-xylene, 3,6-dichloro-p-xylene and 3,6-dibromo-pxylene: DFT study

Abstract: This study explains the vibration and interaction of p-xylene and effect of three elements (fluorine, chlorine and bromine) of the halogen family substitution on it. Basic chemistry of four, compounds p-xylene (PX); 3,6-diflouro-p-xylene (DFPX); 3,6-dichloro-p-xylene (DCPX) and 3,6-dibromo-p-xylene (DBPX) has been explained extensively using theoretical approach. Vibrational energy distribution analysis (VEDA) software was used to study the potential energy distribution (PED) analysis, bond length, bond angles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The natural atomic orbital occupancies of most interacting NBO's of the selected mycotoxins together with their percentage of hybrid atomic orbitals contribution are shown in Table S4. The NBO analysis of these mycotoxins provides information aiding the investigation of the intra and intermolecular bonding as well as accounting for charge transfer [ 31 , 43 , 44 , 45 , 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural atomic orbital occupancies of most interacting NBO's of the selected mycotoxins together with their percentage of hybrid atomic orbitals contribution are shown in Table S4. The NBO analysis of these mycotoxins provides information aiding the investigation of the intra and intermolecular bonding as well as accounting for charge transfer [ 31 , 43 , 44 , 45 , 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…Further, the natural population analysis showed that 170 electrons in the ZEA molecule are distributed on the sub-shells (Table S6 of supporting information). It should be noted that electronegative atoms have the tendency to donate electrons whereas, electropositive atoms tend to accept electrons [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ] Hence, AFM1 molecule has the highest electronegative charge of -0.75723 e accumulated on O 37 and have the tendency to donate electron compared to other investigated mycotoxins. However, ZEA is found to have the highest electropositive charge of 0.83796 e on the C 13 atom (Table S5 of supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…From Fig. 4, Eg is 2.95 eV, which is relatively low [27][28][29][30][31][32], hence excitation from the HOMO to LUMO is easily feasible; this is a basic property of a reactive molecule. Also, the energy gap between HOMO-1 and LUMO + 1 orbitals was determined for a more explicit information about the studied molecule; we obtained Eg to be 4.94 eV.…”
Section: Frontier Molecular Orbital (Fmo) Analysismentioning
confidence: 97%
“…The energy of the HOMO orbital of the dye must lie below the redox potential of the (I À /I 3 À ) couple (À4.80 eV), which is necessary to enable charge regeneration of the dyes. 26,27 DE LUMO is described as the difference between the energy gap of E LUMO of the dyes and E CB of TiO 2 . It is mathematically represented as:…”
Section: Computational Detailsmentioning
confidence: 99%